You can't "solve" these equations. You can factor and distribute, though.
1) Both terms (16x and 8) are divisible by 8. Factor out the 8 so that you have:
8(2x-1)
To check: If you were to distribute the 8 again, you would come back to your original equation, 16x-8.
2) (3x-2y)^2 is the same as (3x-2y)(3x-2y). You can use the FOIL method to distribute. Multiply Firsts, Outsides, Insides, Lasts, then add:
3x * 3x = 9(x^2)
3x * -2y = -6xy
-2y * 3x = -6xy
-2y * -2y = + 4(y^2)
---------------------------
9(x^2) - 12xy + 4(y^2)
Hope that helps.
2007-06-08 07:06:28
·
answer #1
·
answered by I am soooo splendiferous 4
·
0⤊
0⤋
I am not sure what exactly you are asking. If you need to simplify the first equation, you can do that by factoring out the 8, in which case you get 8*(2x - 1) which is just a different form of the original given equations.
For the second one you might need to multiply it out, so you have (3x-2y)(3x-2y) = 9x^2 - 6xy - 6xy + 4y^2 = 9x^2 - 12xy + 4y^2.
Hope this helps, but if not, you need to provide more info about the problem.
2007-06-08 06:57:10
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
for the first part, you will solve for the letter X
16x-8=?
16x=8 ( making 8 a positive integer by taking to the other side of equal)
x= 8/16
x= 2 ( when u divide 16 by 8 u get 2)
thus the value for X is 2.
2007-06-08 07:00:45
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
1) x= 1/2 just substitue the value that yields 0 as result.. can do it grafically aswell you'd get a line parallel to the y axis
2) depends on what u need but first find the values that equate the function to 0, so 3x-2y = 0 , y=3/2x and then it might depend on if you want it greater or smaller than 0
2007-06-08 06:55:56
·
answer #4
·
answered by edcremonese 1
·
0⤊
0⤋
17
2016-04-01 10:16:18
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
1) are you factoring? if so, divide an 8 out of both terms to give you 8(2x-1)
2) (3x-2y)^2 means to multiply (3x-2y)(3x-2y) and you can FOIL where F is first terms, O is outside, I is inside, and L is last
F 3x*3x = 9x^2
O 3x*-2y = -6xy
I -2y*3x = -6xy
L -2y*-2y = 4y^2
add like terms to get 9x^2-12xy+4y^2
2007-06-08 06:54:39
·
answer #6
·
answered by hrhbg 3
·
0⤊
0⤋
16x-8 = ???? need something here, cannot be blank, can't solve
(3x-2y)^2 =
(3x-2y)(3x-2y) =
9x^2 -6xy - 6xy + 4y^2 =
9x^2 -12 xy +4 y^2
2007-06-08 06:54:44
·
answer #7
·
answered by GTB 7
·
0⤊
0⤋
(3x-2y)^2 =
(3x-2y)(3x-2y) =
9x^2 -6xy - 6xy + 4y^2 =
9x^2 -12 xy +4 y^2
2007-06-08 10:38:57
·
answer #8
·
answered by UNIQUE 3
·
0⤊
0⤋